The Chicago Trunk Murder : Law and Justice at the Turn of the Century. - Dale, Elizabeth (Cornell University Press, 2011)
Written with a storyteller's flair for narrative and brimming with historical detail, this book will be must reading for true crime buffs and aficionados of Chicago lore alike.